Samfundsøkonomiske vurderingsmetoder forpolitiske styringsmidler i transportsektoren - Kristensen, Niels Buus (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
The Danish Ministry of Transport has carried out a project with the purpose of investigating the potential for and the social costs of implementing various policy measures in order to reduce the total emissions of CO2 from the transport sector in Denmark. The overall objective has been to improve the basis for policy decisions in the efforts to fulfil the national target for reduction of the CO2-emissions from the transport sector by calculating estimates of the social costs for a long list of potential policy measures. This paper focuses on the developed method for calculation of the social costs related to the implementation various policy measureuch as taxes and other economic instruments, investments and technology improvements and regulations. The approach is based on (partial) welfare econo-mics and takes into account a wide range of cost elements, not just investment and operating costs but also consumer surplus losses and gains as well as a first attempt to estimate the external costs per vehicle kilometre from infrastructure use, congestion, , accidents, air pollution and noise.